Representación de la mujer en los medios de comunicación de Guayaquil, representación, estereotipos, desafíos - Bravo Pacheco, Jhudy Melany (2025)
The media collective thought by producing and reproducing the ways in which society perceives events and determines their acceptance. This qualitative research examines how the media in Guayaquil project a stereotypical and unequal image of women, relegating them to entertainment spaces and roles associated with caregiving, companionship, and motherhood. The authors analyzed the media portrayal of women in Guayaquil’s media, confirming the proposed hypothesis through interviews and content analysis. The findings reveal biases and stereotypes that link women to support and caregiving roles. Based on these conclusions, recommendations are made to develop programs and implement measures that enable Guayaquil’s media to overcome the issue of stereotypes and promote a fair, realistic, and equitable gender representation.